FREE CASH FLOW IN MODERATED CAPITAL STRUCTURE, PROFITABILITY, INSTITUTIONAL OWNERSHIP ON DIVIDEND POLICY - Eduard Ary Binsar Naibaho; Zulfa Naurah (JRAK, 2023)
Dividend policy is influenced by factors that are valid in studies. A factor that has run dividends uncontrollably is free cash flow. By using capital structure, profitability and institutional ownership as independent variables, we examined the effect of capital structure, profitability and institutional ownership on dividend policy with free cash flow as the moderating variable. The test was fulfilled with descriptive, verificative methods and a data panel regression model. Simultaneously, capital structure, profitability and institutional ownership had no positive impact on dividend policy even though free cash flows were collected, it drove capital structure, profitability and institutional ownership unnoticeable to dividend policy. This study is crucial to expanding the perspective on free cash flow and for future research.